National registry-based data of adverse events in Finnish long-term professional homecare in 2009-2019 - Kivimäki, Taina; Stolt, Minna; Katajisto, Jouko; Charalambous, Andreas; Suhonen, Riitta (My University, 2023)
Aims and objectives: The aim of this study was to discover the nature of the adverse events in Finnish long-term professional homecare reported by professionals, and to identify the circumstances in which adverse events occur and their consequences.Background: Adverse events are incidents causing unintended and unnecessary harm to older people at home. Safety is a basic human right and a fundamental prerequisite for independent living among older people at home. Few studies have focused on both long-term professional homecare environment and the safety of older people.Design: The research was a descriptive registry- based study.Methods: This study consisted of adverse events (N= 61248) in Finnish public long- term professional homecare (2009–2019). Data were described using frequencies and percentages. STROBE statement checklist was chosen for reporting the study process.Results: By profession, practical nurses and registered nurses reported the most of adverse events (89.8%). These were either critical incidents (78.3%) or near misses (20.0%) and concerned medicine, injuries and accidents, information flow or manage-ment. Consequences for older people were usually rated from no- harm to moderate harm. For long-term professional homecare, image harm, extra financial costs, no- harm and prolonged care for older people were among the consequences. Personnel frequently observed the older people afterwards and informed older people of ad-verse events, yet some of actions were unknown.Conclusions: Many harmful adverse events are considered harmless for older people. Sometimes this can lead to unmet care needs or missed care. The degree of harm needs to be assessed in terms of physical, mental and social health with the HaiPro reporting system for homecare.Relevance to clinical practice: An understanding and a comprehensive view of the situation and holistic assessment of care needs includes safety and safety risks to increase safety and feeling of safety for older people at home.
Keywords: Adverse event; Descriptive study; Long-term professional homecare; Older people; Registry-based study; Safety